Ekiti agroforestry land use validation data - Vlcek, Jan; Oluyemi Ogunmolu, Mercy (PANGAEA, 2025)
GPS points were collected during July and August 2021 across all 15 Local Government Authorities in Ekiti State, Nigeria. All points were transcribed into an Excel spreadsheet and verified on a map using GEE. GPS points were collected using the GPS Dragon app on a mobile phone with accuracy of within three meters. The land use categories were based on Ashiagbor et al. (2020, doi:10.1016/j.rsase.2020.100349) research and included built-up area/bare land, agricultural land, agroforestry cocoa, full sun cocoa, plantations, primary forest, and secondary forest. 634 points were collected to represent all 7 land types were collected. The data was used for remote sensing analysis utilizing vegetation indices to assess the extent of cocoa agroforestry.
Keywords: Land cover; Nigeria